Association of MRI visible Perivascular Spaces with Early White Matter Injury - Toro, Arturo R.; Lara, Frances Rodriguez; Pinheiro, Adlin; Demissie, Serkalem; Decarli, Charles; Parva, Pedram; Habes, Mohammad; Charidimou, Andreas; Seshadri, Sudha; Maillard, Pauline; Romero, Jose R. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: MRI Visible Perivascular Spaces (PVS) are considered markers of cerebral small vessel disease (CSVD) and may reflect dysfunction of brain perivascular drainage. White matter integrity assessed with Diffusion Tensor Imaging (DTI) provides a sensitive assessment of early brain injury, related vascular risk factors and risk of stroke and dementia. We investigated the relation between PVS and white matter integrity in community-dwelling participants.MATERIALS AND METHODS: Framingham Heart Study (FHS) participants with brain MRI, PVS ratings and DTI measures were included. PVS were rated in the basal ganglia (BG) and centrum semiovale (CS) and categorized into grades I-IV based on counts. We related PVS burden to global DTI measures (free water fraction [FW], fractional anisotropy [FA], peak skeletonized mean diffusivity [PSMD]), Diffusion along perivascular spaces (DTI-ALPS) and voxel-based measures using multivariable linear regression analyses.RESULTS: Among 3,077 participants (57.2 mean age; 53% women), 7% had high burden PVS in the BG and 13% had high burden in the CS. High PVS burden in either or both regions was associated with higher global FW, PSMD, lower global FA and lower DTI-ALPS index in fully adjusted models (p<0.001). Voxel analyses revealed significant associations between high PVS burden in both regions and FW involving ascending, descending, inter and intra-hemispheric tracts (p<0.0001), but not with FA.CONCLUSIONS: PVS burden was associated with early signs of global white matter injury after adjustment for vascular risk factors, suggesting that high PVS burden may represent early brain injury related to CSVD or impaired perivascular function.ABBREVIATIONS: ALPS = Along the perivascular space; PVS = Perivascular Space; CSVD = Cerebral Small Vessel Disease; FW = Free Water; FA = Fractional Anisotropy; MD = Mean Diffusivity; DTI-ALPS = diffusion along perivascular spaces; FHS = Framingham Heart Study; CS = Centrum Semiovale; BG = Basal Ganglia; PSMD = Peak Skeletonized Mean Diffusivity